The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.accounts.7b00161
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Colloidal Nanocrystal Formation and Electrode–Electrolyte Interfaces in Liquids Using TEM

Abstract: Transmission electron microscopy (TEM) has become a powerful analytical tool for addressing unique scientific problems in chemical sciences as well as in materials sciences and other disciplines. There has been a lot of recent interest in the development and applications of liquid phase environmental TEM. In this Account, we review the development and applications of liquid cell TEM for the study of dynamic phenomena at liquid-solid interfaces, focusing on two areas: (1) nucleation, growth, and self-assembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 75 publications
0
38
0
Order By: Relevance
“…In this configuration, a full cell composed of two electrodes and a liquid electrolyte is sandwiched between two electron‐transparent windows and sealed to prevent evaporation of the electrolyte in high‐vacuum TEM. Several in situ TEM studies of electrochemical cells using conventional liquid electrolytes have been reported . Gu et al observed lithiation and delithiation of silicon‐nanowire electrodes in the same environment as a commercial battery system where a conventional liquid electrolyte and Li metal were applied .…”
Section: In Situ Study Of Nanomaterials With External Biasmentioning
confidence: 99%
“…In this configuration, a full cell composed of two electrodes and a liquid electrolyte is sandwiched between two electron‐transparent windows and sealed to prevent evaporation of the electrolyte in high‐vacuum TEM. Several in situ TEM studies of electrochemical cells using conventional liquid electrolytes have been reported . Gu et al observed lithiation and delithiation of silicon‐nanowire electrodes in the same environment as a commercial battery system where a conventional liquid electrolyte and Li metal were applied .…”
Section: In Situ Study Of Nanomaterials With External Biasmentioning
confidence: 99%
“…In 2016, she joined HUST as a lecturer; recently, her research interest lies in teaching and research in characterization of polymer microstructures & nanomaterials. nanoparticles corrosion, 6 self-assembly of nanomaterials, 7 dynamical processes in vivo, 8 in situ electrochemistry 9 and radiolysis induced reaction in energy systems. 10 In this review, we summarize the development of the technology for liquid phase TEM and its application in studying dynamic processes of nanomaterials in recent years (2014-2019).…”
Section: Yan Guomentioning
confidence: 99%
“…All these exciting works about in situ electrochemistry by liquid phase TEM have been summarized in literatures. 4,9,12,68 Additionally, in 2018, Lutz et al have studied the charge/discharge mechanism in Na-O 2 batteries by using fast imaging TEM with electrochemical liquid cells. 69 Fig.…”
Section: In Situ Electrochemistrymentioning
confidence: 99%
“…With the technical advances in electron microscopy, liquid cell transmission electron microscopy (TEM) has acted as a direct and useful tool for observing material transformation in real-time at atomic resolution [16][17][18][19][20][21]. Nanocrystal superlattice formations through self-assembly in solution have been studied by liquid cell TEM [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%